Alterations in blood flow at the optic nerve head in patients with thyroid eye disease using optic coherence tomography angiography - Cao, Shenglan; Liao, Rongfeng; Fang, Chengbo (Frontiers in Medicine, 2025)
IntroductionThis study aimed to evaluate changes in blood flow at the optic nerve head (ONH) in patients with thyroid eye disease (TED) using optical coherence tomography angiography (OCTA).MethodsA total of 59 eyes from 59 patients with TED and 39 eyes from 39 healthy controls (HCs) were included. Patients with TED were categorized into the active and inactive groups based on clinical activity scores. All participants underwent ophthalmological and endocrinological tests. Peripapillary vessel density (VD) and retinal nerve fiber layer thickness (RNFLT) were measured using OCTA. All eyes underwent a 4.5*4.5-mm scan pattern centered on the ONH. The peripapillary region was divided into eight sectors: superior nasal (SN), nasal upper (NU), nasal lower (NL), inferior nasal (IN), inferior temporal (IT), temporal lower (TL), temporal upper (TU), and superior temporal (ST). A correlation analysis was used to explore the association between blood flow changes and relevant factors.ResultsCompared to the eyes of HCs, the eyes of patients in the inactive TED group demonstrated lower radial peripapillary capillary VD, with significant differences observed in the SN and ST sectors of the peripapillary region (p < 0.05). No differences were observed in the peripapillary RNFLT between the groups. Additionally, there was no significant correlation between the whole peripapillary VD and RNFLT or visual functional parameters. Moreover, visual acuity impairment was positively correlated with IN-VD, NU-VD, ST-VD, and NU-RNFLT in the peripapillary region. Intraocular pressure was positively correlated with IN-RNFLT.ConclusionOCTA can detect microvascular ONH changes in patients with TED.